Severe cryptogenic multifocal ulcerous stenosing enteritis. A report of three cases and review of the literature - Kohoutová, Darina; Bures, Jan; Tycová, Vera; Bártová, Jolana; Tachecí, Ilja; Rejchrt, Stanislav; Vacek, Zdenek; Repák, Rudolf; Kopácová, Marcela (Acta medica (Hradec Kralove), 2010)
Cryptogenic multifocal ulcerous stenosing enteritis (CMUSE) is a rare condition characterised by chronic or relapsing moderate ileous episodes resulting from multiple small intestinal strictures, multiple shallow ulcers of the small bowel and favourable therapeutical effect of glucocorticosteroids. The aim of this paper was to evaluate three cases of CMUSE diagnosed within 10 years at a tertiary gastroenterology centre. Three females (35, 50, 60 years) were presented with colicky pain, repeated moderate ileous episodes and weight loss. Multiple fibrous strictures and ulcers of the small bowel were found. All three patients responded to glucocorticosteroid treatment. Tandem tight jejunal stenoses were dilated endoscopically by means of double balloon enteroscopy. In conclusion, CMUSE should always be considered when chronic moderate ileous episodes and multiple small intestinal strictures and ulcers of uncertain aetiology are found. Double balloon enteroscopy enables precise diagnostic work, possible endoscopic treatment of stenoses, may obviate the need for surgery and prevent excessive small bowel resections.
Keywords: tenké střevo; Enteritis; dospělí; vřed; Adult; lidé; Intestine, Small; Intestinal Obstruction; ženské pohlaví; enteritida; lidé středního věku; Humans; Middle Aged; Ulcer; Female; střevní obstrukce